Manajemen Peningkatan Mutu Terpadu Pendidikan Agama Islam di Akademi Manajemen Administrasi Yogyakarta - Hidayatullah (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2021)
This study aims to empirically reveal Total Quality Management (TQM) of education, especially Islamic education. The problems that you want to know in this research are: 1. How is the implementation of integrated total quality management (TQM) for Islamic education at the Yogyakarta Administrative Management Academy? 2. What are the supporting factors for the implementation of TQM for Islamic religious education at the Yogyakarta Administrative Management Academy? 3. What are the obstacles faced in the implementation of TQM Islamic Religious Education at the Yogyakarta Administrative Management Academy? This type of research is qualitative. Using a sociological learning approach. Information gathering is obtained directly from informants through interviews, observations, and documentation. The information analysis method used is information reduction, information display, information verification, and conclusion confirmation. Overall, the implementation of TQM management of Islamic religious education at the Yogyakarta Administrative Management Academy shows significant results both in terms of cognitive and affective. Even so, customer service must be prioritized and improved.